If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2n + -2 = 0 Reorder the terms: -2 + -2n = 0 Solving -2 + -2n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -2n = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -2n = 0 + 2 -2n = 0 + 2 Combine like terms: 0 + 2 = 2 -2n = 2 Divide each side by '-2'. n = -1 Simplifying n = -1
| 54-14=-16-4x | | 7w+2=44 | | 17n-1=25n+47 | | 5a+a=-24 | | 10+5(x-2)=0 | | -25x^2+75x+450=0 | | 3/4x=42 | | (-8z^5)(5z^8)= | | 3a+22=7 | | -8w-12=-4 | | 4*(-8)+9y=14 | | 10lbs-5/8= | | x^4-5x^3+3x^2-15x=0 | | (-8z^5)(5z^5)= | | 10lbs-5/8 | | 20x-4=5x+26 | | Sen^3(4x)+1=0 | | 5-x/20=-4 | | 6.92=-log(x) | | 8(4-6)=32 | | 48=4b | | 2(3x-9)=48 | | (x^2-2x-24)/(x-6) | | 4z/10-2=7 | | x^3-6x^2+36x-296=0 | | 3z/10-1=9 | | 3(x-1)+6= | | a^3-8+3a^2+6a-12ab^2= | | 10x-3-7x=24 | | 6x-83=2x-7 | | 10x-12=9x+3 | | X-20=53 |